The Dynamic Breakup of Soft Glassy Materials - Hayes, Matthew (2022)
The work contained within this thesis is focused on the rheology of soft glassy materials, namely yield stress fluids and how the breakup of these fluids is affected by physical properties such as adhesion, slip and thixotropy. These fluids are of particular interest to several industries, including the oil and gas industry, where their adhesive properties can hamper the drilling process. Questions concerning the adhesive character of yield stress fluids are also of interest in academia where there is still some debate as to the mechanism by which these types of fluids adhere to surfaces. The two most significant sets of experiments in this work made use of a shear rheometer to carry out adhesion tests on samples of kaolin and also laponite clays. In each case the behaviour during the adhesion test was related to the measured shear properties of the samples. The study using kaolin focussed on the role of slip, whilst the study using laponite investigated the role of aging. Additional experiments were also performed with a centrifuge to understand the compaction of kaolin clay under compressive stress. The flow of water / changes in solid volume fraction over time were also followed using x-ray shadowgraphy. This work showed several interesting behaviours that affect adhesion measurements. In the adhesion study on kaolin clay it was shown that despite the breakup being strongly influenced by the concentration of the clay, the start-up behaviour of these experiments is greatly affected by the slip of the experiment. The slip behaviour exhibits a crossover between wall slip and shear-localisation which can be significant enough to influence the final break-up behaviour. Through careful manipulation of the sample history we also showed that the lubrication conditions at the interface can be altered through compaction, modifying the peak adhesion force and the strain at which this occurs. Investigating this compaction further using centrifugation we counterintuitively found that a defined stress does not result in a unique final value of the suspension density. Rather a dense suspension will form a denser final sediment than a less dense suspension when subjected to the same stress. In the adhesion tests on laponite gels we showed that the sample break-up becomes increasingly brittle as the samples age. This can be observed visually, but we also demonstrated that by taking measurements of the sample midpoint and contact angles at the plate surfaces, key rheological properties, such as the yield strain, can be quantified and compared for different samples.